2016
DOI: 10.1186/s40101-016-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body patterns of the range of joint motion in young adults: masculine type and feminine type

Abstract: BackgroundUnderstanding the whole-body patterns of joint flexibility and their related biological and physical factors contributes not only to clinical assessments but also to the fields of human factors and ergonomics. In this study, ranges of motion (ROMs) at limb and trunk joints of young adults were analysed to understand covariation patterns of different joint motions and to identify factors associated with the variation in ROM.MethodsSeventy-eight healthy volunteers (42 males and 36 females) living on Ok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 31 publications
1
17
1
1
Order By: Relevance
“…We found that the presented mean maximal human ankle dorsiflexion value from Roaas and Andersson (1982) was 15 • to 23 • less compared to the dorsiflexion during squat jump and squat lifting (Figure 1). Slightly smaller differences occur when compared to maximal values based on another study (Moromizato et al, 2016). We believe that a part of this difference could result from the definition of the neutral position (subject supine with knee in 45 • flexion) used in Roaas and Andersson (1982) and Moromizato et al (2016), compared to our approach that normalized the data to standing.…”
Section: Range Of Motionmentioning
confidence: 82%
See 2 more Smart Citations
“…We found that the presented mean maximal human ankle dorsiflexion value from Roaas and Andersson (1982) was 15 • to 23 • less compared to the dorsiflexion during squat jump and squat lifting (Figure 1). Slightly smaller differences occur when compared to maximal values based on another study (Moromizato et al, 2016). We believe that a part of this difference could result from the definition of the neutral position (subject supine with knee in 45 • flexion) used in Roaas and Andersson (1982) and Moromizato et al (2016), compared to our approach that normalized the data to standing.…”
Section: Range Of Motionmentioning
confidence: 82%
“…Slightly smaller differences occur when compared to maximal values based on another study (Moromizato et al, 2016). We believe that a part of this difference could result from the definition of the neutral position (subject supine with knee in 45 • flexion) used in Roaas and Andersson (1982) and Moromizato et al (2016), compared to our approach that normalized the data to standing. Further, increased dorsiflexion at the ankle could be possible with increased knee FIGURE 4 | Maximum power vs. maximum moment of the hip, knee, and ankle for all analyzed movements.…”
Section: Range Of Motionmentioning
confidence: 82%
See 1 more Smart Citation
“…Physical parameters of the orthosis links, which were obtained from Solidworks, are given in Table 1; where I i represents moment of inertia, m i is the mass, and l ci is the distance from the i-th joint to the i-th mass center position and l i is the length of the i-th link. Range of motions (ROM) of the orthosis joints has been restricted according to the values in the literature [16]. These ROM values are given in the Table 2.…”
Section: Orthosis Mechanical Designmentioning
confidence: 99%
“…Muscle contractures cause motion in the joints, but whether such motions take place in their full range depends on many factors, including the conditions of the muscles [21]. Nonetheless, it should be mentioned that achieving excessive mobility in the joints (exceeding the physiological norms) may be undesirable and may lead to serious consequences.…”
Section: Introductionmentioning
confidence: 99%